The Impact of Overtraining on the Mental State of Taekwondo Athletes at Jeonstugi Tadulako Club, Palu City - Nur Indah Khafifa Lingu Lembah; Kamarudin Kamarudin; Arief Aditya Rifandy; Andi Sultan Brilin Susandi E,W (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to examine the impact of overtraining on the mental condition of Taekwondo athletes at Jeonstugi Tadulako Club, Palu City. The research problem addressed was how overtraining affects the athletes’ mental condition during the intensive training period preceding competitions. This study employed a qualitative method with a descriptive approach. The informants consisted of 10 participants, comprising 8 Taekwondo athletes as the main informants and 2 coaches as supporting informants, selected through purposive sampling. Data were collected through observation, semi-structured in-depth interviews, audio/video recording, and documentation, and were validated through source and technique triangulation. Data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing/verification. The findings show that training intensity increased substantially as competitions approached, causing most athletes to experience physical fatigue accompanied by mental pressure such as nervousness, tension, and psychological burden. Nevertheless, these conditions did not diminish the athletes’ motivation or concentration during training and competition; several athletes reported that pressure before competition even strengthened their motivation. Athletes applied various recovery strategies, including cooling down, adequate rest, regular sleep patterns, nutritious food intake, and sufficient fluid consumption, while coaches played an important role in designing training programs, monitoring athletes’ conditions, providing motivation, and maintaining both the physical and mental well-being of the athletes. It is concluded that overtraining does affect the mental condition of Taekwondo athletes, but its negative impact can be minimized through appropriate training-load management, optimal recovery practices, and continuous psychosocial support from coaches.